Electroanalytical Sensing of Bromides Using Radiolytically Synthesized Silver Nanoparticle Electrocatalysts - Jadranka Milikić; Ivan Stoševski; Jelena Krstić; Zorica Kačarević-Popović; Šćepan Miljanić; Biljana Šljukić (Journal of Analytical Methods in Chemistry)
Monitoring bromides (Br−) is of crucial importance since bromates, potential human carcinogens, are formed during ozonation of water containing bromides in concentrations >100 μg L−1. Within this study, silver (Ag) and four carbon-supported Ag catalysts were synthesized by the γ-radiation method and their morphology and structure examined using transmission electron microscopy, X–ray diffraction, and UV-Vis analysis. The nanocatalysts were tested for Br− sensing in aqueous media using cyclic voltammetry. All five Ag materials exhibited electroactivity for sensing of Br− ions, with pure Ag catalyst giving the best response to Br− ions presence in terms of the lowest limit of detection. Sensing of bromides was also explored in tap water after addition of bromides suggesting that herein prepared catalysts could be used for bromides detection in real samples. Furthermore, sensing of other halogen ions, namely, chlorides and iodides, was examined, and response due to chloride presence was recorded.